Analisis Dampak Penggunaan Media Sosial Terhadap Indeks Prestasi Kumulatif (IPK) Mahasiswa Prodi Pendidikan Kimia FKIP Unram - Baiq Dewi Aprilia Arnita; Baiq Antika Safitri; Firnaning Ulan; Riadatul Jannah (Journal of Science and Technology: Alpha, 2026)
Social media represents a form of technological advancement that is unavoidable among students. There are various types of social media platforms that are currently popular, including Facebook, Instagram, WhatsApp, TikTok, YouTube, Twitter, and Blogger. Each platform has specific advantages that attract its users, making them spend extended periods navigating the digital world. The use of social media depends on individual behavior as well as environmental influences. This study aims to determine the effect of social media usage on students’ GPA. The research employs a quantitative descriptive and inferential approach, with data analyzed using one-way ANOVA, normality testing, and homogeneity testing. The sample consisted of 31 fourth-semester students from the Chemistry Education study program. The findings indicate that students most commonly use WhatsApp (24%) and Instagram (28%), followed by YouTube (9%), Facebook (10%), TikTok (16%), Line (4%), Snapchat (4%), and X (4%). The survey also revealed a striking result regarding the intensity of social media use: 74% of students reported using social media for more than 4 hours per day, while 26% used it for less than 4 hours. Students who used social media for less than 4 hours had an average GPA of 3.23, whereas those who used it for 4 or more hours had an average GPA of 3.21. The one-way ANOVA analysis resulted in a significance value of 0.908 > 0.05, indicating that H₀ is accepted, meaning there is no significant effect of social media usage duration on students’ GPA. The normality test yielded a significance value of 0.200 > 0.05, indicating that the data are normally distributed. Meanwhile, the homogeneity test produced a significance value of 0.770 > 0.05, showing that the data are homogeneous.